A Comparative Study of Contextual Feminism : Saudi Arabian and Iranian Perspectives - Berry, Vanessa; Petsy Jessy Ismoyo; Novriest Umbu Walangara Nau (Badan Penerbit STIEPARI Press, 2025)
The Feminism movement was born to represent women's long struggle to achieve gender equality and equal rights between women and men. In the context of the Middle East, feminism exists and develops complexly and contextually, especially in countries with Islamic-based legal systems such as Saudi Arabia and Iran. This research aims to analyze the differences in the top-down approach in Saudi Arabia and the bottom-up approach in Iran in influencing the direction of the feminism movement through the lens of postmodern feminism. This research uses a qualitative approach with a comparative study research type. The data that has been collected shows that Saudi Arabia, through the Saudi Vision 2030 program, seeks to increase the role of women in the economy and the public structurally from above or top down, after previously women lived in an environment with very patriarchal policies. In Iran, women face a repressive government system, but that is where the resistance movement from civil society is created. The perspective of postmodern feminism, especially the thoughts of Luce Irigaray, is used to read how women's bodies in these two countries become a political tool as well as a means of symbolic resistance to a system that is so masculine. This research also observes how the internet, digital media, and transnational feminist networks contribute to shaping resistance and awareness in different ways across both contexts. From this study, it can be concluded that feminism cannot be seen as something universal but is shaped by power relations, culture, ideology, and national policy. The feminist movements in Saudi Arabia and Iran reflect how feminism comes in two contrasting elements: one directed by the state, the other emerging organically from society.